Increased Antifungal Drug Resistance in Clinical Isolates of Cryptococcus neoformans in Uganda - Smith, Kyle D.; Achan, Beatrice; Okagaki, Laura H.; Akampurira, Andrew; Kirsten Nielsen,a on behalf of the ASTRO-CM/COAT Team (Antimicrobial agents and chemotherapy, 2015)
Cryptococcal antigen screening is recommended among people living with AIDS when entering HIV care with a CD4 count of <100 cells/μl, and preemptive fluconazole monotherapy treatment is recommended for those with subclinical cryptococcal antigenemia. Yet, knowledge is limited of current antimicrobial resistance in Africa. We examined antifungal drug susceptibility in 198 clinical isolates collected from Kampala, Uganda, between 2010 and 2014 using the CLSI broth microdilution assay. In comparison with two previous studies from 1998 to 1999 that reported an MIC50 of 4 μg/ml and an MIC90 of 8 μg/ml prior to widespread human fluconazole and agricultural azole fungicide usage, we report an upward shift in the fluconazole MIC50 to 8 μg/ml and an MIC90 value of 32 μg/ml, with 31% of isolates with a fluconazole MIC of ≥16 μg/ml. We observed an amphotericin B MIC50 of 0.5 μg/ml and an MIC90 of 1 μg/ml, of which 99.5% of isolates (197 of 198 isolates) were still susceptible. No correlation between MIC and clinical outcome was observed in the context of amphotericin B and fluconazole combination induction therapy. We also analyzed Cryptococcus susceptibility to sertraline, with an MIC50 of 4 μg/ml, suggesting that sertraline is a promising oral, low-cost, available, novel medication and a possible alternative to fluconazole. Although the CLSI broth microdilution assay is ideal to standardize results, limit human bias, and increase assay capacity, such assays are often inaccessible in low-income countries. Thus, we also developed and validated an assay that could easily be implemented in a resource-limited setting, with similar susceptibility results (P = 0.52).